Simulasi Distribusi Laju Dosis Pada Tumor Dan Area Kerja Pada Peralatan Akselerator Elektron Dengan Program MCNP - Tumpal Pandiangan; Stheven Stheven; Valentino Maxmillion (Publikasi dan UKI Press UKI Toraja., 2022)
Linac or linear accelerator is one of the modalities used in radiotherapy. To ensure the quality of radiation dose accepted by the patient, it must be applied quality control on linac, one of which is the PDD (Percentage Depth Dose) value. For this purpose, a method of simulating the distribution of dose rates in tumors was carried out and areas of work with the MCNP program. Simulated values ??of the PDD of electrons and photons with energies of 6MeV and 8MeV have been carried out and distribution of radiation scattering generated using MCNP5 software. The PDD value is 100% for an electron with an energy of 6MeV is at a depth of 40mm while for 8MeV energy is at a depth of 20mm. The depth of photon radiation has a value of 100% at a certain depth that means effective at that depth value.